Malignancies in transplanted patients: multidisciplinary evaluation and switch to mTOR inhibitors after kidney transplantation - experiences from a prospective, clinical, observational study - Hellström, Vivan; Enström, Ylva; Zur-Mühlen, Bengt von; Hagberg, Hans; Laurell, Anna; Nyberg, Filippa; Bäckman, Lars; Opelz, Gerhard; Döhler, Bernd; Holmberg, Lars; Tufveson, Gunnar; Enblad, Gunilla; et al. (Acta oncologica, 2016)
Background Solid organ transplant recipients are at increased risk of developing malignancies. The objective of this prospective, observational, one-armed study was to study the feasibility to add a mammalian target of rapamycin (mTOR) inhibitor to the immunosuppressive regimen in transplanted patients with post-transplant malignancies. During the trial the need to improve identification of post-transplant malignancies and to reassure adequate oncological treatment of these patients became evident. Multidisciplinary team (MDT) evaluation of oncological and immunosuppressive treatments was implemented for all patients with malignancies after renal or combined renal and pancreas transplantation because of the trial.Material and methods At Uppsala University Hospital, Sweden, a MDT consisting of transplant surgeons, nephrologists, oncologists and dermatologists evaluated 120 renal or combined renal and pancreas-transplanted recipients diagnosed with malignancies from September 2006 to July 2012. To identify all malignancies, the population was linked to the Regional Tumor Registry (RTR). We recorded to which extent a switch to mTOR inhibitors was possible and how often the originally planned oncological managements were adjusted. All patients were followed for three years. (ClinicalTrials.gov: NCT02241564).Results In 76 of 120 patients (63%) a switch to mTOR inhibitors was possible. Immunosuppression was interrupted in seven patients (6%), reduced in three patients (2%) and remained unchanged in 34 of 120 patients (28%). Identification of post-transplant malignancies increased significantly after linkage to RTR (p = 0.015). The initially recommended oncological treatment was adjusted in 23 of 44 patients (52%) with solid or hematological malignancies; 36 of these patients (82%) were treated according to national guidelines.Conclusion In two thirds of the patients the immunosuppressive treatment could be changed to an mTOR inhibitor with anti-tumor effects in transplanted patients with post-transplant malignancies. The use of regional tumor registers considerably improved the identification of patients with post-transplant malignancies indicating that post-transplant malignancies might be timely underreported in transplant registers.
Gesehen am 12.05.2020